Analisis Manajemen Risiko Operasional Berdasarkan Rasio Likuiditas dan Aktivitas pada PT Mayora Indah Tbk Tahun 2024 - Inka Niq Masuru; Natalie Mawar Desember; Rifdah Nirmala Sari; Zavicka Alamanda Rizvisal; Alvianus Kristian Sumual (Journal of Economic and Business Advancement, 2025)
This study analyzes the operational risk management of PT Mayora Indah Tbk in 2024, focusing on liquidity, operational efficiency, and capital structure. The data were sourced from the company’s annual financial statements and analyzed using short-term and long-term financial ratios as well as activity ratios. The results show that the current ratio decreased from 3.67 in 2023 to 2.65 in 2024, while the quick ratio dropped from 2.78 to 1.79, indicating high reliance on inventory and potential short-term liquidity issues. Cash flow ratios to current and total liabilities showed negative values, reflecting an imbalance between cash inflows and outflows. Nevertheless, activity ratios improved, with receivables turnover increasing from 4.76 to 5.45 times and inventory turnover from 4.62 to 5.56 times, reflecting effective operational management. Long-term analysis revealed an increase in total debt to total assets from 0.36 to 0.42, although the capital structure remained stable. The study confirms that while PT Mayora Indah Tbk efficiently manages current assets and operational activities, short-term operational risk is elevated due to declining liquidity and negative cash flows.